Upconversion nanoparticle-anchored metal-organic framework nanostructures for remote-controlled cancer optogenetic therapy - Chen, Xiaokai (2025)
Optogenetics, a revolutionary technique utilizing light-sensitive proteins to control cellular functions with high spatiotemporal precision, presents a promising avenue for disease treatment; however, its application in cancer therapy remains constrained by limited research. Herein, we introduce a pioneering strategy for remote-controlled optogenetic cancer therapy, synergistically merging optogenetics with ion therapy, which incorporates ion self-supply, in situ ion channel construction, and near-infrared (NIR) light-activated ion therapy, facilitating remote and noninvasive manipulation of cellular activities in deep tissues and living animals. We report the facile synthesis of water-dispersible upconversion nanoparticle (UCNP)-metal-organic framework (MOF) nanohybrids capable of effectively delivering plasmid DNA to cancer cells, thereby enabling the in situ expression of photoactivatable cation channels. The pH-responsive MOF components serve as a reservoir for metal cations, which are released in the acidic microenvironment of tumors, while the UCNP components function as remote-controlled transducers, converting near-infrared (NIR) light into visible light to activate the cation channels and allowing the cancer influx of released metal cations for ion therapy. The proposed remote-controlled cancer optogenetic therapy demonstrates its effectiveness across multiple tumor models, including subcutaneous colon tumors, subcutaneous breast tumors, and orthotopic breast tumors. This study represents a significant step toward the realization of optogenetics in clinics, with substantial potential for advancing cancer therapy.